Analisis Hubungan Keterampilan Komunikasi Interpersonal dengan Kemampuan Kognitif Siswa SMA pada Materi Dunia Hewan Melalui Model Pembelajaran Picture and Picture : (Analysis of the Relationship between Interpersonal Communication Skills and Cognitive Ability of High School Students on Animal World Materials Through Picture and Picture Learning Model) - Ananda Anggitia Aftaroh Anggit; Billyardi Ramdhan; Gina Nuranti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This research is a quasi-experimental study that aims to determine the relationship between interpersonal communication skills and cognitive abilities of high school students on animal world material through the picture and picture learning model for class X MA At-Tahsiniyyah for the academic year 2021/2022. The research instrument was arranged based on 5 aspects of interpersonal communication, namely 1) openness, 2) empathy, 3) supportive attitude, 4) positive attitude, 5) equality. Meanwhile, the cognitive ability research instrument will be written in the form of a pretsest-posttest which refers to indicators of cognitive ability based on the revised Bloom's Taxonomy, namely remembering (C1), understanding (C2), applying (C3), analyzing (C4), evaluating (C5) and creating (C1). C6). The results showed that there was a relationship between interpersonal communication skills and the cognitive abilities of high school students in the animal world with a Paerson correlation value of 0.679 with a strong correlation category. Key words: Interpersonal Communication Skills, Cognitive Abilities, Picture And Picture Learning Models. Â ABSTRAK Penelitian ini merupakan penelitian quasi eksperimen yang bertujuan untuk mengetahui hubungan keterampilan komunikasi interpersonal dan kemmapuan kognitif siswa SMA pada materi dunia hewan melalui model pembelajaran picture and picture kelas X MA At-Tahsiniyyah tahun ajaran 2021/2022. Instrument penelitian disusun berdasarkan 5 aspek komunikasi interpersonal yaitu keterbukaan, empati, sikap mendukung, sikap positif, dan kesetaraan. Sedangkan instrumen penelitian kemampuan kognitif akan dituangkan dalam bentuk pretsest-posttest yang mengacu pada indikator kemampuan kognitif berdasarkan Taksonomi Bloom revisi yaitu mengingat (C1), memahami (C2), mengaplikasikan (C3), menganalisis(C4), mengevaluasi (C5) dan mencipta (C6). Hasil penelitian menunjukan adanya hubungan antara keterampilan komunikasi interpersonal dengan kemmapuan kognitif siswa SMA pada materi dunia hewan dengan nilai paerson correlation 0,679 dengan kategori korelasi kuat. Kata kunci: Keterampilan Komunikasi Interpersonal, Kemampuan Kognitif, Model Pembelajaran Picture And Picture.